Positive Deviance pada Status Gizi Balita - Pepi Hapitria Djaswadi Dasuki Djauhar Ismail (Berita Kedokteran Masyarakat (BKM), 2011)
Background: Positive Deviance (PD) is a ‘power’ based approach having a belief that in each community there are certain individuals as the actors of ‘positive deviance’ that own specific habit and behavior. They might find out better ways to prevent nutritional deficiency compared to their surroundings that possess the same resource and face the same risk as well.Objective: To find out PD behavior in poor family towards under-five children’s nutritional status in Astanajapura Health Center working area of Cirebon District.Method: The study used a case control study design and in-depth interview. Subjects were under-five children 6-59 months of age. Data collection used a questioner and interview. Data analysis used univariate, bivariate, and multivariate analysis with logistic regression to determine OR and 95% CI of the effect of PD behavior towards under-five good nutritional status.Result: Under-five good nutritional status was significantly related to PDbehavior (OR=7.43; 95% CI=1.89–29.17). The other factors affecting under-five good nutritional status were maternal education (OR=6.63; 95%CI=1.63–23.90) and under-five age (OR=4.05; 95% CI=1.16–14.10).Conclusion: Under-five good nutritional status had a significant relationship with PD behavior.Keywords: nutritional status, positive deviance behavior, under-five children